SEROPREVALENCIA DE Toxoplasma gondii EN LLAMAS DE DOS FUNDOS GANADEROS DE LA PROVINCIA DE MELGAR, PUNO - Marcas C., Gualberto (2004)
The aim of this study was to determine the seroprevalence of Toxoplasma gondii in female llamas from two farms located in the Melgar province, Puno. A total of 284 blood samples were tested using the indirect immunofluorescence test (IFAT) to detect antibodies against T. gondii. The results showed that 47.5 + 5.8% (135/284) of the samples had antibodies and they increased with age. The seroprevalence from birth till 2 years, 2- 4 years, >4-6 years, and >6 years was 33.8 ± 11.0, 51.2 ± 10.8, 56.8 ± 14.6, and 50.6 ± 10.5%, respectively. There were significant differences (p<0.05) in the frecuency of female reactors between farms. Age and farm variables were considered as risk factors for the infection with Toxoplasma gondii (p<0.0001).